Relationship of prenatal maternal obesity and diabetes to offspring neurodevelopmental and psychiatric disorders: a narrative review - Kong LH; Chen XX; Gissler M; Lavebratt C (NATURE PUBLISHING GROUP, 2022)
Obesity and diabetes is a worldwide public health problem among women of reproductive age. This narrative review highlights recent epidemiological studies regarding associations of maternal obesity and diabetes with neurodevelopmental and psychiatric disorders in offspring, and provides an overview of plausible underlying mechanisms and challenges for future human studies. A comprehensive search strategy selected terms that corresponded to the domains of interest (maternal obesity, different types of diabetes, offspring cognitive functions and neuropsychiatric disorders). The databases searched for articles published between January 2010 and April 2019 were PubMed, Web of Science and CINAHL. Evidence from epidemiological studies strongly suggests that maternal pre-pregnancy obesity is associated with increased risks for autism spectrum disorder, attention-deficit hyperactivity disorder and cognitive dysfunction with modest effect sizes, and that maternal diabetes is associated with the risk of the former two disorders. The influence of maternal obesity on other psychiatric disorders is less well studied, but there are reports of associations with increased risks for offspring depression, anxiety, schizophrenia and eating disorders, at modest effect sizes. It remains unclear whether these associations are due to intrauterine mechanisms or explained by confounding family-based sociodemographic, lifestyle and genetic factors. The plausible underlying mechanisms have been explored primarily in animal models, and are yet to be further investigated in human studies.